Use of Lean and CAHPS Surgical Care Survey to Improve Patients' Experiences with Surgical Care. (22nd July 2016) - Jiang, Nancy; Malkin, Benjamin D.
Abstract : Objectives: (1) Measure patients' experiences with surgical care using the Consumer Assessment of Healthcare Providers and Systems (CAHPS) Surgical Care Survey. (2) Use lean thinking to analyze and improve quality of patient care. Study Design: A prospective quality improvement study. Setting: Hospital‐based otolaryngology clinic. Subjects and Methods: The CAHPS Surgical Care Survey was distributed to 17 surgical patients to determine their perception of the current state of care. Survey results were analyzed with lean thinking, and changes were made to improve critical areas. A second set of surveys was distributed to 10 patients to assess the success of the interventions immediately and 2 months later. The data were analyzed with the Mann‐Whitney U test. Results: Seventeen patients completed the CAHPS Surgical Care Survey to determine the initial state. A3 Thinking was used to analyze the results and design an improvement. Overall positive patient experience was 57% at the postoperative visit with 3 key aspects of care: time spent during visit, encouragement to ask questions, show of respect to the patient. Two causes were postulated; then, solution approaches were developed and tested in a series of rapid experiments. Two groups of 10 patients completed the CAHPS Surgical Care Survey to determine the postintervention state. Overall positive patient experience significantly improved to 93% ( U = 474, P <. 001) and 83% ( U = 546, P =. 009) immediately and 2 months later, respectively. Conclusion: Lean thinking helps to eliminate defects by breaking down complex problem solving into a scientific process. When combined with the CAHPS Surgical Care Survey, it can be successfully used to improve patients' surgical experiences.